The screening of heart disease by cardiac auscultation and electrocardiography examination in pregnant women in Puskesmas Tegalrejo, Yogyakarta, Indonesia - Lucia Kris Dinarti; Detty Siti Nurdiati; Anggoro Budi Hartopo; Fika Humaeda Assilmi; Alifia Salsabila; Vera Dewanto; Armalya Pritazahra; Muhammad Reyhan Hadwiono; Muhammad Gahan Satwiko; Erna Ashlihah Rochmat; Nu Pravitasari; Dyah Wulan Anggrahini (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Women adapt to pregnancy through multi-organ system physiologic changes, including cardiovascular adaptations. These changes affect those with pre-existing cardiovascular problems differently, and subsequently lead to higher probability of death caused by cardiovascular diseases during pregnancy. Therefore, detection of cardiovascular disease early in pregnancy is important to lower maternal morbidity and mortality by providing prompt and adequate management. This study aimed to evaluate and test the feasibility of integrating 12-lead electrocardiogram (ECG) examination and antenatal care (ANC) screening as a simple and effective method for early detection of heart abnormality in pregnant woman. Pregnant women were recruited in this study in any trimester who attended ANC for a routine pregnancy examination in Puskesmas Tegalrejo Yogyakarta. The subjects underwent primary screening which focused on cardiac auscultation and 12-lead ECG examinations, and those who had abnormal findings were further followed-up in secondary screening by using trans-thoracic echocardiography to confirm heart abnormality. A total of 523 pregnant women from Puskesmas Tegalrejo were included in this study. 15 (2.8%) pregnant woman were suspected to have heart abnormalities; from those, 3 (0.5%) were found with heart murmurs with abnormal ECG readings, 1 (0.19%) had heart murmurs with normal ECG results, and 11 (2.1%) had abnormal ECG readings only. The secondary screening of those patients resulted in 1 (0.19%) pregnant woman who was diagnosed with Atrial Septal Defect. Our study found that among 15 patients identified with suspected ECG abnormalities, one mother who underwent ANC was newly diagnosed with a pre-existing cardiac abnormality. Our study concluded this screening method is a simple and feasible integrated heart screening program that can be implemented widely. We hope this integrated heart screening program may benefit pregnant women who may have cardiac abnormalities to be detected as early as possible, thus reducing maternal morbidity and mortality.